(untitled) (Bioresearch Communications, 2024)
Background/Objective: Women of reproductive age (WRA) in developing countries experience a double burden of malnutrition, which adversely impacts their health and the well-being of future generations. Addressing this issue requires updated data to guide effective interventions. Therefore, this study aimed to assess the prevalence and factors associated with malnutrition among WRA in Bangladesh using recent national data. Methodology: This study analyzed data from the Bangladesh Demographic and Health Survey (BDHS)-2022, which included a nationally representative sample of 8,593 WRA between 15 and 49 years. The outcome variables were malnutrition: underweight (BMI< 18.5 kg/m2), overweight (BMI 23 to<27.5 kg/m2), and obesity (BMI ≥27.5 kg/m2) stratified according to rural-urban residence. Multiple logistic regression was employed to identify factors associated with malnutrition. Results: Overall, 55.5% of WRA were overweight or obese, with a significantly higher prevalence in urban areas (63.7%) compared to rural areas (52.3%). Conversely, approximately 10% of WRA were underweight, with rural areas showing a higher prevalence (11.2%) than urban areas (6.7%). Factors associated with increased odds of overweight or obesity in both urban and rural settings included older age, higher educational attainment, having more children, and residing in wealthier households. Conversely, younger age, breastfeeding mothers, lower education, and wealth levels were associated with higher odds of being underweight in both areas. Conclusion: The study clearly highlights that undernutrition and overnutrition are prevalent in Bangladesh. To address the dual burden of malnutrition among WRA in Bangladesh, targeted interventions, including nutrition education, a nutritional support program, and a healthy food and nutrition environment, are required to improve nutritional status and health outcomes. Bioresearch Commu. 11(1): 1711-1727, 2025 (January)